2007
DOI: 10.1177/0960327107070570
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase and monoamine oxidase activity in relation to mercury levels in the cerebral cortex of wild river otters

Abstract: Mercury (Hg) is a global pollutant that is neurotoxic to many mammalian species. The present study was conducted to determine if the bioaccumulation of Hg by wild river otters ( Lontra canadensis) could be related to variations in the activities of key neurochemical enzymes. River otters were collected from Ontario and Nova Scotia (Canada) during the trapping seasons, spanning 2002-2004, and their brains were dissected into the cerebral cortex and cerebellum. The activities of cholinesterase (ChE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 38 publications
5
46
0
Order By: Relevance
“…Previous in vivo studies have found similar relationships between MeHg exposure and MAO activity, although wildlife studies are uncommon in the literature. In wild river otters, a negative correlation between MAO activity and THg or MeHg concentration was observed in the cerebral cortex but not the cerebellum (Basu et al 2007a), and in wild polar bears, MAO activity in the occipital lobe showed a negative correlative relationship with total Hg concentration (Krey et al 2014). In laboratory studies, decreased MAO activity was observed in the brain stem of rat pups exposed to MeHg chloride in utero (Beyrouty et al 2006), and in the cortex and cerebellum of rats exposed to MeHg (Chakrabarti et al 1998).…”
Section: Dopaminergic Signaling Pathwaymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous in vivo studies have found similar relationships between MeHg exposure and MAO activity, although wildlife studies are uncommon in the literature. In wild river otters, a negative correlation between MAO activity and THg or MeHg concentration was observed in the cerebral cortex but not the cerebellum (Basu et al 2007a), and in wild polar bears, MAO activity in the occipital lobe showed a negative correlative relationship with total Hg concentration (Krey et al 2014). In laboratory studies, decreased MAO activity was observed in the brain stem of rat pups exposed to MeHg chloride in utero (Beyrouty et al 2006), and in the cortex and cerebellum of rats exposed to MeHg (Chakrabarti et al 1998).…”
Section: Dopaminergic Signaling Pathwaymentioning
confidence: 98%
“…Cholinergic signaling pathways have been linked to essential physiological processes including learning, memory, stress response, and modulation of sensory information; the disturbance of dopaminergic neurotransmission is related to psychiatric symptoms in humans (Reis et al 2009). The muscarinic acetylcholine receptor (mAChR) from the cholinergic signaling pathway and monoamine oxidase B (MAO-B) from the dopaminergic signaling pathway are known to be sensitive to MeHg exposure (Chakrabarti et al 1998;Coccini et al 2000;Basu et al 2005aBasu et al , 2006aBasu et al , 2006bBasu et al , 2007aBeyrouty et al 2006;Stamler et al 2006;Coccini et al 2007). The disruption of either of these signaling pathways due to increased THg accumulation in the Arctic could adversely affect beluga whales in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between H gi and the dopamine receptor was also observed in wild river otters and wild mink (Basu et al, 2005a). A negative relationship between GABAa receptor binding levels and Hg was observed in captive mink , while monoamine oxidase and acetylcholinesterase activities were negatively correlated to brain Hg in wild river otters (Basu et al, 2007b). (Hamilton et al, 2011;Scheuhammer et al, 2008) Herring gulls (Larus argentatus) -ns -ns (Rutkiewicz et al, 2010) Little brown bats (Myotis lucifugus)…”
Section: A Backgroundmentioning
confidence: 88%
“…Neurochemical changes may represent early and reversible indicators o f neurological harm because they occur prior to the onset o f overt functional or structural damage Manzo et al, 2001). Neurochemical biomarkers from diverse signaling pathways have been used to assess potential neurotoxicological risk o f MeHg exposure in terrestrial mammals, avian species and marine mammals; results have suggested that environmental exposure to MeHg was associated with neurochemical variation in diverse species (Basu et al, 2005a;Basu et al, 2006a;Basu et al, 2005c;Basu et al, 2007b;Basu et al, 2007c;Basu et al, 2009;Hamilton et al, 2011;Rutkiewicz et al, 2010;Scheuhammer et al, 2008). Therefore, a neurochemical biomarker approach may provide valuable information about potential neurotoxicity in wildlife exposed to MeHg and other neurotoxins.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation